Implementation of Data Warehouse for Food Sales Strategy Using Snowflake Schema Model - Rima Tamara Aldisa; Mohammad Aldinugroho Abdullah (IJISTECH (International Journal of Information System and Technology), 2022)
Waroenk kids collage is a restaurant that sells various types of food menus and is located in Indonesia, Jakarta. This restaurant has data that accumulates and accumulates without any continuation of that data. This is not supported by the final report. Therefore, it is necessary to build a data warehouse that can be used as information for waroenk restaurant owners for college children. One of the important processes in the operation of the data warehouse is the process of copying data from the operational database. Before the data enters the data warehouse, the ETL (extract, transform, load) process is carried out on the data. This scheme is designed for the data warehouse at Waroenk Anak Kampusan using the Snowflake Schema model. The results of the research show that the Waroenk Anak Kampusan data warehouse has four tables (product table, price table, service table and customer dimensions), has one real table, namely the Sales table. All sales data can be monitored by the owner and can find out the total sales data.